THE EFFECT OF STAFFING AS ONE FUNCTION MANAGEMENT AT INONA INCUBATOR ACEH BESAR AGAINST PERFORMANCE EMPLOYEE - Febyolla Presilawati; M. Dharma Nauval; Zuhri Kurniawan Khalid (Universitas Muhammadiyah Metro, 2022)
Inona Incubator is a company which located in Aceh Besar and engaged in animal husbandry by producing egg incubators. This research using descriptive statistical analysis and linear regression analysis to find out influence component staffing to performance employee. Based on results which obtained, the independent variables are recruitment, selection, training, reward and punishment, and development together have a significant influence on performance employee. Whereas results t-test showing t count as big as 2,936 with significance 0.007 between variables recruitment with performance employee. Based on results the, variable recruitment has influence which big to employee performance. Results t count on variable selection as big as 2,228 and significance as big as 0.036. Just like the recruitment variable, based on these results it can be concluded that the selection variable has a significant effect on employee performance. The training variable gets the results of the t-test with a t count of -0.149 and a significance 0.883 which indicates that the training variable has no effect on employee performance. Then the reward and punishment variables get results t-test with t count of 1.699 with a significance of 0.102. While the variable development gets results t-test with t count 0.531 and significance 0.601. Based on these results, the variables of reward and punishment as well as development do not have the influence that big against performance employee.